Trigona Honey Bee Cultivation Business Contribution (Trigona Sp) on The Income of Farm Households in Pemepek Village Pringgarata Sub-District Central Lombok Regency - Sari, Dewi Sahmin Puspita; Rosadi, Narita Amni; Rengganis, Baiq Santi (Management Science Doctoral Program, Pasundan University, Bandung, Indonesia, 2023)
The objectives of this research are: (1) To determine the costs and income of honey bee cultivation businesses Trigona sp In Pemepek Village, Pringgarata Sub-District, Central Lombok Regency; (2) Knowing the magnitude of the contribution of the honey bee cultivation business Trigona sp on farmer household income; (3) Knowing what obstacles are faced by honey bee cultivation businesses Trigona sp. In this research the method used is the descriptive method. Determination of the sample area was carried out using purposive sampling, while the data collection technique was carried out using a census. The research results show that: (1) Average production costs for honey bee cultivation businesses Trigona sp amounting to IDR 134,663,- per one production or IDR 403,989,- per year (3 production times). The average honey production produced is 0.11 liters per stop or 2.15 liters per production or 6.45 liters per year with a price at the farmer level of IDR 300,000, so that the average revenue is IDR 646,000 per one. times production or IDR 1,938,000 per year. And the average income of honey bee farmers is IDR 511,337 per production or IDR 1,534,011 per year. (2) Contribution of honey bee business Trigona sp to farmer household income of IDR 1,501,789,- or 14.11% of the total income of IDR 10,874,204,- per year, which comes from farming IDR 5,085,193,- or 46.76% and non-agricultural business IDR 4,255,000,- or 39.13%; (3) The main obstacles faced by honey bee business actors Trigona sp are weak financial management of honey bee cultivation businesses, reduced raw materials for bees' main consumption which are produced from various trees or plants that produce resin, nectar and pollen, reduced honey stocks, the presence of pests and diseases, low consumer confidence in the quality of honey.